Hacking a terror network the silent threat of covert channels - Rogers, Russ. (Rockland, Mass. : Syngress, 2005)
Written by a certified Arabic linguist from the Defense Language Institute with extensive background in decoding encrypted communications, this cyber-thriller uses a fictional narrative to provide a fascinating and realistic "insider's look" into technically sophisticated covert terrorist communications over the Internet. The accompanying CD-ROM allows readers to "hack along" with the story line, by viewing the same Web sites described in the book containing encrypted, covert communications. Hacking a Terror NETWORK addresses the technical possibilities of Covert Channels in combination with a very real concern: Terrorism. The fictional story follows the planning of a terrorist plot against the United States where the terrorists use various means of Covert Channels to communicate and hide their trail. Loyal US agents must locate and decode these terrorist plots before innocent American citizens are harmed. The technology covered in the book is both real and thought provoking. Readers can realize the threat posed by these technologies by using the information included in the CD-ROM. The fictional websites, transfer logs, and other technical information are given exactly as they would be found in the real world, leaving the reader to test their own ability to decode the terrorist plot. Cyber-Thriller focusing on increasing threat of terrorism throughout the world. Provides a fascinating look at covert forms of communications used by terrorists over the Internet. Accompanying CD-ROM allows users to "hack along" with the fictional narrative within the book to decrypyt.
Foreword -- Prologue -- The mind of terror -- Unseen planning -- Making friends -- One step closer -- Over the line -- Images of death -- The real assignment -- Creating the code -- Over the edge -- Biding time -- Covert channels -- Facing the truth -- Taking command -- Racing the clock -- Losing control -- Heightened motivation -- Chasing ghosts -- Taking back control -- Vengeance for deceit -- Elmininating false positives -- Gaining a finger hold -- Compressing timelines -- A plan comes together -- Turning fiction into reality.
Keywords: Terrorism -- Prevention -- Computer network resources; Cyberterrorism -- Prevention; Internet -- Security measures; Internet -- Political aspects; Terrorists -- United States -- Fiction; Electronic books